2003
DOI: 10.1615/critreveukaryotgeneexpr.v13.i24.130
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the Genes Encoding Human and Mouse Osteoactivin

Abstract: Osteoactivin (OA) is more highly expressed in the bones of osteopetrotic mutant rats (op/op) than in those of their normal littermates and is the homologue of human nmb, a cDNA more highly expressed in melanoma-derived cell lines of low metastatic potential, and of mouse DC-HIL, which has been implicated in endothelial cell adhesion. The human OA gene is found on chromosome 7p15.1 and consists of 11 exons spanning 28.3 kb. Murine OA is encoded by a highly similar gene of 11 exons spanning 20.2 kb on mouse chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 0 publications
1
46
2
Order By: Relevance
“…21 Human and mouse OA are expressed in primary osteoblast cultures at all stages of differentiation. 22 The highest univariate lod-score for TR BMD was 1.89 on chromosome 6q27 near marker D6S446 at 170 Mb. In this case, the bivariate analysis of trait pairs LS/TR BMD gave a maximum lod-score of 1.75 in the same area.…”
Section: Discussionmentioning
confidence: 97%
“…21 Human and mouse OA are expressed in primary osteoblast cultures at all stages of differentiation. 22 The highest univariate lod-score for TR BMD was 1.89 on chromosome 6q27 near marker D6S446 at 170 Mb. In this case, the bivariate analysis of trait pairs LS/TR BMD gave a maximum lod-score of 1.75 in the same area.…”
Section: Discussionmentioning
confidence: 97%
“…1, A-C). Prior studies suggested that gpnmb expression in mice, rats, and humans was enriched in osteoblasts (37)(38)(39), the DC line XS52 (28), retinal pigment epithelial cells, and melanocytes (40,41), and, more recently, in osteoclast-like cells (42). From some of theses studies, gpnmb was previously named osteoactivin and DC heparan sulfate proteoglycan dependent integrin ligand (dc.hil).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, osteoactivin is considered as a downstream-mediator of bone morphogenic protein-2 (BMP-2), which is and has been widely applied in bone tissue engineering models. With its highly osteo-inductive effects on ostegenic differentiation and its secretion by osteoblasts, it directly regulates their endogenous BMP-2 release mechanism (Abdelmagid et al, 2008;Owen et al, 2003;Utsunomiya et al, 2012).…”
Section: Discussionmentioning
confidence: 99%